Macronutrient composition of street food in Central Asia: Bishkek, Kyrgyzstan - Albuquerque, G (2020)
Background: Urban areas in central Asia are currently undergoing nutrition transition. Street food is very popular, but the specific foods available and their nutritional composition are unknown. The aim was to describe the availability and macronutrient composition of street foods in Bishkek, Kyrgyzstan. Results: Trained interviewers collected data on street food vending sites' characteristics and food availability (n = 596). Samples of the most commonly available foods and drinks were collected (n = 80 homemade;n = 40 industrial). Macronutrients were quantified through chemical analysis. Fruit, beverages, and food other than fruit were available in 4.0%, 61.7%, and 81.0% of the vending sites, respectively. Among those selling food other than fruit, 56.5% sold only homemade (e.g., bread, main dishes, snacks, pastries, sandwiches, and cakes), 23.3% both homemade and industrial and 20.2% only industrial foods (e.g., bread, snacks, pastries, cakes, and cookies). Homemade foods presented the highest energy/serving (median kcal/serving: 357 versus 145,p < .001). A high content in saturated and trans-fatty acids was observed in some homemade traditional dishes and snacks, reaching, respectively, 30.2 g/serving and 2.9 g/serving (in homemademanty,a traditional dish). Tea and soft drinks were available in over 50% of the vending sites selling beverages. Conclusion: The high availability of street food in Bishkek highlights its importance for this urban population. Traditional snacks, dishes, and beverages coexist with more westernized products. The variability in energy, macronutrients, and lipid profile of homemade and industrial products reflects heterogeneous culinary practices and ingredients. Policies promoting the availability of healthy foods and ingredients should be implemented.